Cereal phenolic contents as affected by variety and environment. Issue 5 (30th July 2018) - Rao, Shiwangni; Schwarz, Lachlan J.; Santhakumar, Abishek B.; Chinkwo, Kenneth A.; Blanchard, Christopher L.
Abstract: Background and objectives: Phenolic compounds found in cereals have been shown to possess antioxidant activity that has ensured an increased interest in their health beneficial properties. This review analyzed studies investigating the phenolic content of rice, barley, oats, and sorghum grown in different geographical locations and the effect environmental factors have on them. Findings: From the studies reviewed, it was identified that whole grain pigmented cereals exhibited phenolic profiles with polyphenols such as anthocyanins, proanthocyanidins, and their derivatives that translated to higher total phenolic content and antioxidant activity. Variation in phenolic content was also observed in cereal species grown in different geographical locations and when subjected to variable levels of salinity, water, and temperature. Conclusions: Despite the increasing body of knowledge on the phenolic content of cereals, studies focusing on the effect of environment on cereal phenolic content are limited; hence, more research is warranted. Significance and novelty: This review examines literature to provide a holistic understanding of how environment plays a role in the regulation of phenolic metabolites in cereals such as oats with a focus on pigmented varieties of rice, barley, and sorghum.